Global, regional, and national burden of thyroid cancer in women of child-bearing age, 1990 to 2021 and predictions to 2035: An analysis of the global burden of disease study 2021 - Jiang, Tao; Bin, Li; Liu, Huiting; Gao, Cailiang; Liu, Xue (Frontiers in Endocrinology, 2025)
BackgroundThyroid cancer has increased globally, particularly among young women, highlighting the need for research on its epidemiological characteristics and disease burden in women of child-bearing age. This study aimed to analyze the global and regional burden of thyroid cancer from 1990 to 2021, focusing on women of child-bearing age, and to predict trends up to 2035.MethodsThis study analyzed the global and regional burden of thyroid cancer from 1990 to 2021, focusing on women of child-bearing age, using data from the Global Burden of Disease Study. Key indicators assessed included incidence, mortality, and disability-adjusted life years (DALYs) of thyroid cancer in different regions. Statistical analysis techniques were employed to compare the burden across regions and countries, examining the effects of age, sex, and socio-demographic index (SDI) on disease burden. The Bayesian Age-Period-Cohort model was used to predict the incidence, mortality, and DALYs of thyroid cancer from 2022 to 2035.ResultsGlobally, in 2021, there were 67,558 new cases of thyroid cancer among women of child-bearing age, with 3,260 deaths and 206,508 DALYs. Compared to 1990, new cases increased by 156.86%, deaths increased by 52.33%, and DALYs increased by 61.72%. The age-standardized incidence rate (ASIR), mortality rate (ASMR), and DALYs rate (ASDR) per 100,000 population were 3.37, 0.16, and 10.38, respectively. The Estimated Annual Percentage Change (EAPC) for ASIR was 1.47, indicating an increasing trend, whereas the EAPCs for ASMR and ASDR were -0.35 and -0.05, showing decreasing trends. The burden of thyroid cancer among patients with women of child-bearing age exhibited a significant age-related trend, peaking in the 45–49 age group. There were significant regional and national variations in thyroid cancer burden, which are closely related to the SDI. By 2035, a notable increase in the incidence, mortality, and DALYs associated with thyroid cancer among women of child-bearing age has been predicted globally.ConclusionOver the past 30 years, thyroid cancer incidence among women has significantly increased globally, with slightly declining mortality and DALYs rates. Significant regional and national variations are closely linked to the SDI. As the population ages and incidence continues to rise, targeted prevention and treatment strategies, particularly in low SDI regions, are crucial to effectively reduce mortality and DALYs.